[PP.29.05] ALDOSTERONE IS NOT ASSOCIATED WITH INSULIN-MEDIATED MICROVASCULAR RECRUITMENT AND INSULIN SENSITIVITY IN ABDOMINALLY OBESE, BUT OTHERWISE HEALTY MEN. (September 2016) - SCHÜTTEN, M.; Kusters, Y.; Houben, A.; Schalkwijk, C.; Joris, P.; Plat, J.; Mensink, R.; de Leeuw, P.W.; Stehouwer, C.
Abstract : Objective: Increased aldosterone levels have been implicated in the pathogenesis of obesity-associated insulin resistance, which may be partly attributable to aldosterone synthesis in adipocytes. We hypothesized that aldosterone-induced impairment of insulin-mediated microvascular recruitment in skeletal muscle contributes to the insulin resistant state as observed in obesity. We therefore investigated whether aldosterone levels are related to insulin-mediated muscle microvascular recruitment and insulin sensitivity in lean and abdominally obese men, and whether improvement of muscle microvascular function and insulin sensitivity following weight loss might be explained by reduced aldosterone levels. Design and method: In 25 lean (age (mean ± SD) 47 ± 18 years, waist circumference 85 ± 6 cm) and 53 abdominally obese (age 50 ± 13 years, waist circumference 106 ± 4 cm) otherwise healthy men, renin and aldosterone levels were measured with ELISA. Insulin-mediated microvascular recruitment (IMMR) in forearm skeletal muscle and glucose infusion rate (GIR; measure of insulin sensitivity) were assessed by means of contrast-enhanced ultrasound before and during a hyperinsulinaemic clamp. The abdominally obese men were randomized to an 8-week weight loss intervention or their habitual diet. Thereafter, measurements of renin, aldosterone, IMMR, and GIR were repeated. Results: IMMR and GIR were lower in the abdominally obese as compared to the lean men (IMMR: lean 44 ± 41%, obese −3.9 ± 27%, p < 0.01; GIR: lean 6.8 ± 1.8 mg/kg/min, obese: 4.0 ± 1.3 mg/kg/min, p < 0.01). Aldosterone and renin levels were not different between both groups (aldosterone (median [IQR]): lean 225 [176–316] pg/mL, obese 234 [170–315] pg/mL, p = 0.71; renin: lean 671 [519–872] pg/mL, obese 615 [535–786] pg/mL, p = 0.30). Aldosterone levels did not correlate with IMMR or insulin sensitivity. In the weight loss group, waist circumference decreased, and IMMR and GIR improved significantly compared to the weight stable group. Aldosterone and renin levels, however, remained unchanged. Conclusions: Our data suggest that in abdominally obese, but otherwise healthy men, aldosterone does not contribute to the development of muscle microvascular dysfunction and insulin resistance. Possibly, the role of aldosterone becomes more prominent with increasing severity of obesity.